A high thermal conductivity silicone resin and its preparation process
By adopting shear, magnetic guidance and vacuum treatment methods in the production process of high thermal conductivity silicone resins, the problems of uneven dispersion of fillers and insufficient thermal conductivity in the prior art are solved, and more efficient thermal conductivity and better mechanical and electrical properties are achieved.
Patent Information
- Application Number
- CN202411686283.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The thermal conductivity of existing high-thermal conductivity silicone resins is insufficient, and it is difficult for traditional production processes to achieve uniform dispersion and efficient orientation of fillers, resulting in increased local thermal resistance and decreased overall thermal conductivity.
Using a process of combining shear, magnetic guidance and vacuum treatment, the fillers are arranged in the shear direction in the matrix through high-speed shearing, forming a continuous thermal conduction path, and the nanoparticles are arranged in an orderly manner through a strong electromagnetic field, reducing interface thermal resistance and ensuring that the silicone resin fills into the pores of the filler skeleton.
The thermal conductivity of the material is improved, an uninterrupted thermal conductivity network is formed, local thermal resistance is reduced, and the mechanical and electrical insulation properties of the material are enhanced.
Smart Images

Figure CN119192858B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to a high thermal conductivity organic silicon resin and a preparation process thereof. Background Art
[0002] Silicone resin refers to a class of polymers based on silicon-oxygen bonds (Si-O-Si). High thermal conductivity silicone resin refers to a silicone resin with originally low thermal conductivity that has higher thermal conductivity by adding certain high thermal conductivity filler materials (such as metal oxide particles, graphene, etc.) to the silicone resin. It usually has good heat resistance, electrical insulation and stability, and can effectively conduct heat. Silicone resin can be liquid or solid and is cured according to different application scenarios. It is suitable for application scenarios that require good thermal management performance, such as LED packaging, electronic device heat sink pads, etc.
[0003] With the trend of miniaturization and integration of electronic devices, the requirements for efficient heat dissipation materials are increasing, especially the heat dissipation materials between LED chips and heat sinks. The existing high thermal conductivity silicone resin still has the problem of insufficient thermal conductivity. The traditional production process is difficult to achieve uniform dispersion and efficient orientation of fillers. The uneven dispersion of fillers in the matrix will lead to increased local thermal resistance. The interface thermal resistance between the filler and the matrix is high, which leads to a decrease in the overall thermal conductivity. Therefore, the present invention provides a high thermal conductivity silicone resin and a preparation process thereof to solve the above problems. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention aims to provide a high thermal conductivity silicone resin and a preparation process thereof.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] The first aspect of the present invention is to provide a process for preparing a high thermal conductive silicone resin, comprising the following steps:
[0007] (1) Filler pretreatment: dispersing a high thermal conductivity nanofiller in a solvent, adjusting the pH value, adding a silane coupling agent for surface modification, and obtaining a modified dispersion of the filler;
[0008] (2) Mixing raw materials: adding the modified dispersion of the filler into the silicone resin matrix, adding one or more high thermal conductive nanofillers and a crosslinking agent, and performing shearing treatment using a high-speed shearing machine to ensure uniform dispersion and achieve shear force orientation of the filler;
[0009] (3) Orientation of fillers: Pour the mixed solution into a mold and place it in a strong electromagnetic field so that the fillers are arranged in the matrix along the direction of the electromagnetic field to form an effective heat conduction network;
[0010] (4) Vacuum degassing: The filled mold is placed in a vacuum filling device to remove bubbles by vacuum filling, while filling the silicone resin into the pores of the filler skeleton;
[0011] (5) Heat treatment and curing: The filled sample is placed in an oven for cross-linking and curing. After complete curing, it is naturally cooled to room temperature to obtain a high thermal conductivity silicone resin.
[0012] Furthermore, the silicone resin matrix is one of fluorine-containing silicone resin, polydimethylsiloxane, and epoxy-modified silicone resin, the high thermal conductivity nanofiller includes at least two of boron nitride (BN), aluminum oxide (Al2O3), silicon carbide (SiC), and graphene, and the morphology of the high thermal conductivity nanofiller includes at least two of flake, spherical, and fibrous.
[0013] Furthermore, the silane coupling agent is one of KH550, KH560, and KH570, the cross-linking agent is one of methyltrimethoxysilane, vinyltrimethoxysilane, and diisopropylbenzene peroxide, and the addition amount of the cross-linking agent is 1%-5% of the total raw material mass.
[0014] Furthermore, the solvent includes N,N-dimethylacetamide, toluene and xylene.
[0015] Furthermore, the shear rate of the high-speed shearing machine is 5000 rpm, and the processing time is 30 minutes.
[0016] Furthermore, the magnetic field strength of the strong electromagnetic field is 0.3-0.5 T, and the treatment time is 10 minutes to 1 hour.
[0017] Furthermore, the vacuum degree of the vacuum filling device is 10 -2 Up to 10 -3 mbar.
[0018] Furthermore, the conditions for the heat treatment and curing are a temperature of 150° C. and a heat preservation time of 2 hours.
[0019] Furthermore, the mixed solution is modified by a rheology modifier before being poured into the mold, and the rheology modifier includes a thixotropic agent and a thickener.
[0020] Another aspect of the present invention is to provide a high thermal conductivity organic silicone resin, which is prepared by using the above-mentioned preparation process of the high thermal conductivity organic silicone resin.
[0021] The beneficial effects achieved by the present invention are:
[0022] 1. The present invention combines shearing, magnetic guidance and vacuum treatment. Through high-speed shearing, the filler is arranged in the matrix along the shearing direction to form a continuous heat conduction path. At the same time, the filler is evenly dispersed in the matrix to reduce agglomeration. Through the action of a strong electromagnetic field, the nanoparticles are arranged in an orderly manner in the matrix to improve the effectiveness of the heat conduction path. The bubbles in the material are removed under vacuum conditions to ensure that the silicone resin is filled into the pores of the filler skeleton, thereby improving the uniformity and integrity of the material, reducing the interface thermal resistance, and thus improving the thermal conductivity.
[0023] 2. The present invention uses fillers with different morphologies, such as flake fillers oriented within the film plane to form high thermal conductivity within the plane, and non-flake fillers to form thermal conductive connections between the flake fillers to enhance the thermal conductivity in the thickness direction, thereby forming an uninterrupted thermal conductive network and improving the thermal conductivity of the material.
[0024] 3. The present invention uses a silane coupling agent to modify the surface of part of the filler, thereby changing the charge properties of the filler surface. The modified filler is oriented in a specific direction in the electromagnetic field to form a continuous heat conduction path. The unmodified filler can be better filled between the modified fillers to form a denser heat conduction network, thereby improving the overall thermal conductivity.
[0025] 4. The present invention can improve the mechanical properties of the material by optimizing the type and form of the filler. The uniform dispersion of the non-flaky filler can reduce stress concentration and improve the durability of the material.
[0026] 5. The present invention uses a silane coupling agent to modify the surface of the filler, which can improve the electrical insulation performance of the material. Optimizing the orientation and dispersion of the filler can improve the performance of the material in an electromagnetic environment and ensure the electromagnetic compatibility of electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The present invention is a flow chart of the preparation process of the high thermal conductivity silicone resin. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further described below in conjunction with specific implementation methods.
[0029] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0031] Example 1
[0032] A high thermal conductivity silicone resin comprises the following components: a silicone resin matrix (fluorine-containing silicone resin), a high thermal conductivity nanofiller (flaky boron nitride and spherical aluminum oxide), a silane coupling agent (KH550) and a crosslinking agent (methyltrimethoxysilane).
[0033] A preparation process of a high thermal conductivity silicone resin, such as Figure 1 As shown, the following steps are included:
[0034] (1) Filler pretreatment: 10 parts by mass of flake boron nitride was dispersed in 100 parts by volume of a solvent (N,N-dimethylacetamide), the pH value was adjusted to 5, 1 part by mass of a silane coupling agent KH550 was slowly added dropwise, stirred for hydrolysis for 30 minutes, heated in a water bath to 80°C, stirred for 2 hours, and then centrifuged and dried to obtain a modified dispersion of the boron nitride filler;
[0035] (2) Raw material mixing: Add the modified dispersion of the boron nitride filler to 100 parts by mass of the fluorine-containing silicone resin, add 10 parts by mass of spherical alumina and 2 parts by mass of methyltrimethoxysilane, and use a high-speed shearing machine to shear at 5000 rpm for 30 minutes to achieve shear force orientation of the filler;
[0036] (3) Orientation of fillers: Pour the mixed solution into a mold and place the mold in a magnetic field with a magnetic field strength of 0.3 T for 1 hour to allow the fillers to be aligned in the direction of the electromagnetic field in the matrix to form an effective heat conduction network;
[0037] (4) Vacuum degassing: Place the filled mold in a vacuum filling device to remove bubbles by vacuum filling, and fill the silicone resin into the pores of the filler skeleton at a vacuum degree of 10 -2 mbar;
[0038] (5) Heat treatment and curing: The filled sample is placed in an oven and heated to 150°C for 2 hours to ensure the cross-linking and curing of the material. After complete curing, it is naturally cooled to room temperature to obtain a high thermal conductivity silicone resin.
[0039] Example 2
[0040] A high thermal conductivity organic silicone resin comprises the following components: an organic silicone resin matrix (polydimethylsiloxane), a high thermal conductivity nano filler (spherical boron nitride and flaky silicon carbide), a silane coupling agent (KH560) and a crosslinking agent (vinyltrimethoxysilane).
[0041] A preparation process of a high thermal conductivity silicone resin, such as Figure 1 As shown, the following steps are included:
[0042] (1) Filler pretreatment: 10 parts by mass of spherical boron nitride was dispersed in 100 parts by volume of a solvent (toluene), the pH value was adjusted to 5, 1 part by mass of a silane coupling agent KH560 was slowly added dropwise, stirred for hydrolysis for 30 minutes, heated in a water bath to 80° C., stirred for 2 hours, and then centrifuged and dried to obtain a modified dispersion of the boron nitride filler;
[0043] (2) Raw material mixing: Add the modified dispersion of the boron nitride filler to 100 parts by mass of polydimethylsiloxane, add 10 parts by mass of flaky silicon carbide and 2 parts by mass of vinyltrimethoxysilane, and use a high-speed shearing machine to shear at 5000 rpm for 30 minutes to achieve shear force orientation of the filler;
[0044] (3) Orientation of fillers: Pour the mixed solution into a mold and place the mold in a magnetic field with a magnetic field strength of 0.4 T for 30 min, so that the fillers are arranged in the direction of the electromagnetic field in the matrix to form an effective heat conduction network;
[0045] (4) Vacuum degassing: Place the filled mold in a vacuum filling device to remove bubbles by vacuum filling, and fill the silicone resin into the pores of the filler skeleton at a vacuum degree of 10 -3 mbar;
[0046] (5) Heat treatment and curing: The filled sample is placed in an oven and heated to 150°C for 2 hours to ensure the cross-linking and curing of the material. After complete curing, it is naturally cooled to room temperature to obtain a high thermal conductivity silicone resin.
[0047] Example 3
[0048] A high thermal conductivity silicone resin comprises the following components: a silicone resin matrix (epoxy modified silicone resin), a high thermal conductivity nano filler (flake boron nitride and spherical graphene), a silane coupling agent (KH570) and a crosslinking agent (diisopropylbenzene peroxide).
[0049] A preparation process of a high thermal conductivity silicone resin, such as Figure 1 As shown, the following steps are included:
[0050] (1) Filler pretreatment: 10 parts by mass of flake boron nitride was dispersed in 100 parts by volume of a solvent (xylene), the pH value was adjusted to 5, 1 part by mass of a silane coupling agent KH570 was slowly added dropwise, stirred for hydrolysis for 30 minutes, heated in a water bath to 80° C., stirred for 2 hours, and then centrifuged and dried to obtain a modified dispersion of the boron nitride filler;
[0051] (2) Mixing raw materials: adding a modified dispersion of a boron nitride filler to 100 parts by weight of an epoxy-modified silicone resin, adding 10 parts by weight of spherical graphene and 2 parts by weight of diisopropylbenzene peroxide, and shearing the mixture at 5000 rpm for 30 minutes using a high-speed shearing machine to achieve shear force orientation of the filler;
[0052] (3) Orientation of fillers: Pour the mixed solution into a mold and place the mold in a magnetic field with a magnetic field strength of 0.5 T for 10 minutes to align the fillers in the matrix along the direction of the electromagnetic field to form an effective heat conduction network;
[0053] (4) Vacuum degassing: Place the filled mold in a vacuum filling device to remove bubbles by vacuum filling, and fill the silicone resin into the pores of the filler skeleton at a vacuum degree of 10 -2 mbar;
[0054] (5) Heat treatment and curing: The filled sample is placed in an oven and heated to 150°C for 2 hours to ensure the cross-linking and curing of the material. After complete curing, it is naturally cooled to room temperature to obtain a high thermal conductivity silicone resin.
[0055] Comparative Example
[0056] A conventional thermal conductive silicone grease (hereinafter referred to as a high thermal conductive silicone resin) includes vinyl silicone oil with a viscosity of 100 cs, aluminum oxide, and a silane coupling agent. The preparation process of the high thermal conductive silicone resin is as follows: 100 parts by mass of vinyl silicone oil and 700 parts by mass of aluminum oxide (the surfaces of which are modified by a silane coupling agent) are mixed at a rotation speed of 800 RPM, stirring and mixing thoroughly, then stopping stirring, and cooling to obtain the high thermal conductive silicone resin.
[0057] Performance test: The high thermal conductivity silicone resins obtained in Examples 1-3 and the comparative example were subjected to tests related to thermal conductivity, mechanical properties and electrical properties;
[0058] 1. Thermal conductivity test: According to GB / T 30031-2013 "Determination of thermal conductivity and thermal diffusivity of plastics - laser flash method", a high thermal conductivity silicone resin is made into a sample with a thickness of 1.5 mm and a diameter of 11 mm. The sample is placed on the sample stage of the laser flash method thermal conductivity meter. A laser pulse is used to irradiate one side of the sample, and the temperature response curve of the other side of the sample is recorded. The temperature response curve is analyzed by software to calculate the thermal diffusivity of the sample. The thermal conductivity is calculated by combining the density and specific heat capacity of the sample.
[0059] 2. Tensile strength test: According to GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets", make a sample with a length of 115mm, a width of 10mm and a thickness of 1.5mm with high thermal conductivity silicone resin, fix the sample on the tensile fixture of the universal material testing machine, ensure that the clamping position is firm, start the testing machine, and perform a tensile test at a tensile speed of 50mm / min. Record the tensile force-displacement curve of the sample until the sample breaks, record the maximum tensile force and elongation at break, and calculate the tensile strength.
[0060] 3. Breakdown voltage test: According to GB / T 1410-2006 "Determination of volume resistivity and surface resistivity of solid insulating materials", make a sample with a thickness of 1.5mm and a diameter of 25mm from the high thermal conductive silicone resin. Place the sample between electrodes with a distance of 2.5mm between the electrodes to ensure good contact between the electrodes and the sample. Slowly increase the voltage at a rate of 100V / s and gradually increase the voltage. Record the voltage value when the sample breaks down.
[0061] The test results are shown in Table 1.
[0062] Table 1 Test results of high thermal conductivity silicone resin performance
[0063]
[0064] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A process for preparing a high thermal conductivity silicone resin, characterized in that: The following steps are involved: (1) Filler pretreatment: dispersing a high thermal conductivity nanofiller in a solvent, adjusting the pH value, adding a silane coupling agent for surface modification, and obtaining a modified dispersion of the filler; (2) Raw material mixing: adding the modified dispersion of the filler into the silicone resin matrix, adding another high thermal conductivity nanofiller and a crosslinking agent, and performing shearing treatment using a high-speed shearing machine; (3) Orientation of fillers: Pour the mixed solution into a mold and place it in a strong electromagnetic field so that the fillers are arranged in the matrix along the direction of the electromagnetic field to form a heat-conducting network; (4) Vacuum degassing: The filled mold is placed in a vacuum filling device to remove bubbles by vacuum filling, while filling the silicone resin into the pores of the filler skeleton; (5) Heat treatment and curing: The filled sample is placed in an oven for cross-linking and curing. After complete curing, it is naturally cooled to room temperature to obtain a high thermal conductivity silicone resin; The high thermal conductivity nano filler includes at least two of boron nitride, aluminum oxide, silicon carbide, and graphene, and the morphology of the high thermal conductivity nano filler includes at least two of flake, spherical, and fibrous.
2. A process for preparing a highly thermally conductive silicone resin according to claim 1, characterized in that: The organic silicon resin matrix is one of fluorine-containing organic silicon resin, polydimethylsiloxane and epoxy-modified organic silicon resin.
3. The process for preparing a highly thermally conductive silicone resin according to claim 1, characterized in that: The silane coupling agent is one of KH550, KH560 and KH570, the cross-linking agent is one of methyltrimethoxysilane, vinyltrimethoxysilane and dicumyl peroxide, and the addition amount of the cross-linking agent is 1%-5% of the total raw material mass.
4. The process for preparing a highly thermally conductive silicone resin according to claim 1, characterized in that: The solvent includes N,N-dimethylacetamide, toluene and xylene.
5. The process for preparing a highly thermally conductive silicone resin according to claim 1, characterized in that: The shear rate of the high-speed shearing machine is 5000 rpm, and the processing time is 30 minutes.
6. The process for preparing a highly thermally conductive silicone resin according to claim 1, characterized in that: The magnetic field strength of the strong electromagnetic field is 0.3-0.5 T, and the treatment time is 10 minutes to 1 hour.
7. The process for preparing a high thermal conductive silicone resin according to claim 1, characterized in that: The vacuum degree of the vacuum filling device is 10 -2 Up to 10 -3 mbar.
8. The process for preparing a high thermal conductive silicone resin according to claim 1, characterized in that: The conditions for the heat treatment and curing are a temperature of 150° C. and a heat preservation time of 2 hours.
9. The process for preparing a highly thermally conductive silicone resin according to claim 1, characterized in that: The mixed solution is modified by a rheology modifier before being poured into the mold. The rheology modifier includes a thixotropic agent and a thickener.
10. A high thermal conductivity silicone resin, characterized in that: The high thermal conductivity silicone resin is prepared by the preparation process of any one of claims 1 to 9.
Citation Information
Patent Citations
Anisotropic insulating thermal-conductive sheet and preparation method thereof
CN110229367A
Interplanar high-thermal-conductivity composite material and preparation method thereof
CN114031943A